THE IMPACT OF VOCABULARY BUILDING ON IMPROVINGSTUDENTS’ SPEAKING SKILLS IN CLASS IX RIYADHUSSALAM ISLAMIC JUNIOR HIGH SCHOOL - Iim Khairunnisa, Diana Maulidiya Almaida Tuzakiyyah, Ani Sumaeratu Aini, Novi Aulia, Nur Fadhillah A (Jurnal Pendidikan dan Penelitian Serumpun Mendidik, 2024)
English, as an international language, plays a crucial role in global communication. However, speaking proficiency, particularly in Indonesia, remains a challenging skill to acquire among students. This study aims to explore the influence of vocabulary development on the speaking skills of 16 ninth-grade students at Riyadhussalam Islamic Junior High School. This study revealed that students faced speaking challenges due to insufficient vocabulary. They struggled to express thoughts and often mispronounced or misspelled words. This research investigates whether enhancing vocabulary significantly affects students' speaking skills. It employs qualitative and quantitative methods, utilizing interviews, pre-test, post-test, and questionnaires. Interviews with teachers assessed initial speaking instruction conditions, while pre- and post-tests measured students' speaking abilities before and after vocabulary intervention. Questionnaires gauged student responses to the vocabulary development program. The study involved vocabulary practice in speaking activities such as sentence construction, discussions, conversations, and simulations..